2016
DOI: 10.1108/lodj-05-2014-0092
|View full text |Cite
|
Sign up to set email alerts
|

Can incivility impair team’s creative performance through paralyzing employee’s knowledge sharing? A multi-level approach

Abstract: Purpose – The purpose of this paper is to examine how a supervisor’s incivility in teams impact team’s creative performance through the mediating factor of knowledge sharing intention among team members. Moreover, the moderating role of collaborative climate was investigated as protector against leaders’ incivility. Design/methodology/approach – The proposed multi-level model was tested by surveying 312 health care providers nested withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
46
0
16

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 132 publications
3
46
0
16
Order By: Relevance
“…Consistent with Beattie and Griffin's () argument, individuals who experience workplace incivility may have lower work engagement compared to those who are not treated uncivilly. The results are also consistent with Sharifirad's () work regarding the negative impact of a leader's incivility on the creative performance of teams.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Consistent with Beattie and Griffin's () argument, individuals who experience workplace incivility may have lower work engagement compared to those who are not treated uncivilly. The results are also consistent with Sharifirad's () work regarding the negative impact of a leader's incivility on the creative performance of teams.…”
Section: Discussionsupporting
confidence: 87%
“…The negative influence of workplace incivility on two types of job performance has been argued in previous studies (e.g. Porath and Erez 2009;Porath, Foulk and Erez 2015;Porath and Pearson 2010;Sharifirad 2016). However, our current understanding of the conditions under which the influence of workplace incivility on job performance occurs is far from comprehensive (Jawahar and Schreurs 2018;.…”
mentioning
confidence: 86%
“…In particular, exposure to workplace incivility is stressful for employees and depletes their personal resource reservoirs, thereby threatening their ability to fulfill their job duties (Estes & Wang, 2008;Lim et al, 2008;Sliter, Sliter, & Jex, 2012). Previous studies reveal a broad range of negative consequences of this type of workplace adversity, including interpersonal deviance (Wu, Zhang, Chiu, Kwan, & He, 2014), withdrawal behavior (Lim & Cortina, 2005), and absenteeism (Sliter et al, 2012), as well as a tendency to stop engaging in positive behaviors such as creativity (Sharifirad, 2016), self-enhancement efforts (Chen et al, 2013), or citizenship behaviors (Taylor, Bedeian, & Kluemper, 2012;Thompson, Carlson, Hunter, & Whitten, 2016).…”
Section: Dissatisfaction and Political Skillmentioning
confidence: 99%
“…Workplace incivility, as an interpersonal form of mistreatment, has been associated with a variety of undesirable outcomes that adversely affect employees’ physical and psychological well‐being, job outcomes, and interpersonal relationships (see a review, Schilpzand, Pater and Erez ). However, among the existing literature on multiple consequences of incivility, few studies have paid sufficient attention to the association between workplace incivility and outcomes concerning creative performance (for exceptions, see Hur, Moon and Jun ; Porath and Erez ; Sharifirad ).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Within a service management context, Hur, Moon and Jun () found incivility from customers and co‐workers decreases service employees’ creativity through the sequentially mediating role of emotional exhaustion and intrinsic motivation. At team level, Sharifirad () suggested that supervisor incivility negatively affects team creative performance by weakening employees’ intention to share knowledge.…”
mentioning
confidence: 99%